Home confinement and mental health problems during the Covid-19 pandemic among the population aged 50 and older: A gender perspective - Patrícia Silva; Fátima Barbosa; Manuela André; Alice Delerue Matos (Elsevier, 2022)
Home confinement during the Covid-19 pandemic is usually associated with worsening mental health. In the case of older adults, although they have been identified as a vulnerable group in terms of mental health, the results of studies on the relationship between home confinement and mental health are not consistent and few studies have adopted a gender perspective.Using data from the SHARE Corona Survey (2020), we aimed to analyse the role of gender on the relationship between home confinement and increased depression in individuals aged 50 and over living in Europe and Israel.Our study shows that, although women reported increased depression/sadness during the Covid-19 pandemic more often than men, it was the latter who experienced the greatest increase.